Formation of modern diplomatic terms and their adaptation into national languages - Xaydarova, Dilafruz (The Lingua Spectrum, 2025)
The system of diplomatic terms is a complex and multifaceted phenomenon that occupies an important place as one of the main sources of lexical enrichment of a language. Due to the close interrelation of diplomacy with various social spheres such as international law, politics, culture, and economics, the terminology of this field is constantly evolving and renewing. Therefore, modern diplomatic terminology has developed into an independent semantic system within the language of international communication, forming a significant linguistic layer that ensures the clarity and effectiveness of intergovernmental communication. This article analyzes the formation of modern diplomatic terms and their adaptation into national languages, particularly into the Uzbek language, from linguistic and translation studies perspectives. The research highlights the stages of formation of diplomatic terminology in the international system, as well as their morphological and semantic characteristics, and the mechanisms of their adoption from Spanish into Uzbek. Based on examples such as embajada, nota verbal, asilo político, acuerdo marco, and reunión bilateral, the article examines the phonetic, semantic, and functional adaptation processes of diplomatic terms. The author emphasizes the importance of maintaining equivalence, neutrality, and cultural context in the translation of diplomatic terminology. The study employs comparative, descriptive, and contextual analysis methods. The article of the research lies in the fact that Spanish-origin diplomatic terms adopted into Uzbek are examined for the first time from a linguistic and pragmatic perspective. The results of the study have practical significance for further research in diplomatic language, translation studies, and international communication culture.